LEPTIN LEVEL IN NON DIABETIC POPULATION WITH AND WITHOUT NON ALCOHOLIC FATTY LIVER (NAFL) - Sofia, Noor Asyiqah (Acta Interna The Journal of Internal Medicine, 2012)
ABSTRACTBackground. Non alcoholic fatty liver disease (NAFLD) is a prevalent condition associated with obesity and insulin resistance. Leptin is an adipokine which plays role in decreasing food intake and controlling energy utilization. The role of leptin pathogenesis of NAFLD remains unclear. Former studies associated with the role of leptin in NAFL were never conducted in diabetic patients. Therefore we aimed to analyze the difference of leptin level in non diabetic population between subjects with and without non alcoholic fatty liver disease.Method. This was a non matching case control study in general check up polyclinic Dr.Sardjito Hospital Yogyakarta. The inclusion criteria were aged 30-60 years old, no history of alcohol consumption > 20 gr/day, no diabetes mellitus. The exclusion criteria were viral hepatitis (B and C), rapid weight loss, steroid therapy, and pregnancy.Â Diagnosis of NAFL was based on bright liver imaging from ultrasonography.Result. There were 48 subjects consist of 23 subjects with NAFL and 25 subjects without NAFL. Mean of leptin level in NAFL group was higher than non NAFL group and this difference was statistically significant (20.29 + 15.73 ng/ml and 12.27 + 10.1 ng/ml; p=0.040).Conclusion. The conclusion of this study was leptin level significantly higher in non diabetic population with NAFL compared with non NAFL.Â Keywords: Â leptin, non diabetic, non alcoholic fatty liver